2023
DOI: 10.3389/fsurg.2023.1157684
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted radical cystectomy with intracorporeal reconstruction of urinary diversion by mechanical stapler: prospective evaluation of early and late complications

Abstract: IntroductionRadical cystectomy with pelvic lymph node dissection is the gold standard treatment for non-metastatic muscle-invasive bladder cancer and high-risk non–muscle-invasive bladder cancer. For years, the traditional open surgery approach was the only viable option. The widespread of robotic surgery led to its employment also in radical cystectomy to reduce complication rates and improve functional outcomes. Regardless of the type of approach, radical cystectomy is a procedure with high morbidity and not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In the first five years of follow-up, 45% of patients had urinary diversion-related complications, and after 15 years of follow-up, this percentage had risen to over 54% [ 63 ]. A recent study reported that the overall late complications of RC were 40.2%, and the most common late complications were hydronephrosis (11.6%) and urinary tract infections (20.5%) [ 64 ]. There are diverse functional complications, including emptying dysfunction, neobladder continence problems, stoma complications in patients with ileal conduit, stenosis of uretero-intestinal anastomosis, urolithiasis, urinary infections, worsening of renal function, metabolic acidosis, and vitamin B12 deficiency [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the first five years of follow-up, 45% of patients had urinary diversion-related complications, and after 15 years of follow-up, this percentage had risen to over 54% [ 63 ]. A recent study reported that the overall late complications of RC were 40.2%, and the most common late complications were hydronephrosis (11.6%) and urinary tract infections (20.5%) [ 64 ]. There are diverse functional complications, including emptying dysfunction, neobladder continence problems, stoma complications in patients with ileal conduit, stenosis of uretero-intestinal anastomosis, urolithiasis, urinary infections, worsening of renal function, metabolic acidosis, and vitamin B12 deficiency [ 65 ].…”
Section: Discussionmentioning
confidence: 99%